AI for creatives : unlocking expressive digital potential - Ching, Vivian; Mothi, Dinesh (CRC Press : Taylor & Francis Group : Auerbach Book, 2025)
AI for Creatives: Unlocking Expressive Digital Potential takes you on a dynamic journey into the future of creativity, where AI is reshaping how creators approach their craft. According to a 2023 UNESCO report, the global creative industries are valued at an astounding USD